Lessons in forging sustainable partnerships for rice self-sufficiency in CALABARZON, MIMAROPA, and Bicol Regions - Amit, Mayo Grace C.; Querijero, Nelson Jose Vincent B. (2012)
In an era of polyvocality and multi-stakeholder partnership, the authors trace the beginnings of an initiative of the University of the Philippine Los Baños (UPLB) and other program partners in addressing food security concern through a devolved agricultural extension service. Building on inter-organizational relations theory and partnership building, UPLB served as a partnership broker among the provincial governments, municipal governments, Department of Agriculture Regional Field Units, the local state universities and colleges, and civil organizations. The paper documents the beginnings and nuances in brokering partnerships and cites the challenges associated with promoting transdisciplinarity in UPLB known to protect specialized domains.
Keywords: Food; Food security; Rice security programs